The concept of human rights in the scientific heritage of Boris Safarovich Ebzeev. On the 75th anniversary of the scientist - Komkova, Galina Nikolaevna; Zametina, Tamara Vladimirovna; Kosolapov, Mikhail F. (Известия Саратовского университета. Новая серия: Серия «Экономика. Управление. Право»)
This year marks the 75th anniversary of the famous Russian constitutional scholar, statesman and public figure, judge of the highest qualification class, Honored Scientist of the Russian Federation, Honored Lawyer of the Russian Federation, Doctor of Law, Professor Boris Safarovich Ebzeev. The article is devoted to the analysis of the concept of human rights, which has become one of the main areas of his scientific research. The article presents the main stages of the scientist’s research and professional activity, his system of views on the institution of constitutional rights and freedoms, and highlights his contribution to the development of modern Russian science of constitutional law. The authors analyze the main works (monographs, articles, speeches) by B. S. Ebzeev, the legal positions that he formulated and that were set out in the Dissenting Opinions of the decisions of the Constitutional Court of the Russian Federation on the issues of constitutional rights and freedoms of man. The main ideas of the scientist are systematically presented, which may be significant for researchers, and important for the further development of domestic legal science, formation of the worldview of young researchers, preservation of scientific traditions and continuity, creation of new ideas and concepts.